The modification of the thrombin generation assay for the clinical assessment of hypercoagulability in patients receiving heparin therapy. (12th October 2021) - Benoit, Remi; Nougier, Christophe; Desmurs‐Clavel, Helene; Simon, Marie; Dargaud, Yesim
Abstract: Background: Heparin diminishes thrombin generation (TG) because it decreases the survival time of thrombin in plasma. Under heparin therapy, the TG curve therefore does not reflect the true hemostatic status of the patient. Aim: We investigated how far the in vitro addition of a heparin antagonist can restore the underlying TG capacity. Materials & Methods: Five different heparin antagonists were tested: polybrene, protamine sulfate, heparinase type 1, heparinase HEP‐TEM, and (Z‐GGR)2 ‐rhodamine (P2Rho). Results and Conclusion: Polybrene, P2Rho, and heparinase HEP‐TEM effectively neutralized heparin at prophylactic and therapeutical doses of both low molecular weight and unfractionated heparin. The advantages and limits of each molecule and the most favorable combinations of TG‐trigger and antagonist are discussed.